New Topology LNA Architecture using Inductive Drain Feedback Technique for Wireless Application - Kamil bin Pongot; Othman A.R; Zakaria Z; Suaidi M.K; Hamidon A.H (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper presents a design of a  single LNA cascaded with double stage cascoded LNA amplifiers using an inductive drain feedback technique. The amplifier it is implemented using superHEMT FHX76LP transistor devices.  The designed circuit is simulated with  Ansoft Designer SV.  The LNA was designed using  inductive drain feedback, inductive generation to the source, and the T-network as a matching technique was used at the input and output terminal. The  low noise amplifier (LNA) provides a gain (S21) of 68.94 dB and the noise figure (NF) of 0.64 dB. The return loss (S12) output reflection (S22) and input reflection (S11) are -88.39,-17.37 and –15.77 dB respectively. The measurement shows a 3-dB bandwidth  of 1.72 GHz and stability are 4.54 more than 1 has been achieved. The input sensitivity is -92 dBm  exceeded the standards required by IEEE 802.16.